Students' continuance of using e-learning system: A review of conceptual frameworks - Nur Shamsiah, Abdul Rahman; A. N., Rosman; Noor Azida, Sahabudin (IOP Publishing, 2020)
This research presented a review of conceptual framework regarded to find the factors of students' continued use of online learning system. The outcomes were reported according to a systematic review on the recent research articles (from 2013 until 2019) related with continued use of e-Learning system. From review of theoretical models and related theories we recommend to use Unified Theory of Acceptance and Use of Technology (UTAUT) to measure students' intention to continued use of e-learning system. The discussion of this research obtained revealed that the most common factors influence students' intention to continued use e-learning are performance expectancy, effort expectancy, social, self-efficacy, perceived usefulness and behavioral intention to continued use.